2005
DOI: 10.1111/j.1365-2648.2005.03592.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐Based Stress Reduction as supportive therapy in cancer care: systematic review

Abstract: AimTo systematically review and critically appraise the evidence on the effectiveness of Mindfulness-Based Stress Reduction (MBSR) for cancer supportive care. MethodsA comprehensive search of major biomedical databases including Medline, EMBASE, CINAHL, PsycINFO and the Cochrane Library was conducted. Specialist complementary and alternative medicine (CAM) databases including AMED and CISCOM were also searched. Additionally, efforts were made to identify unpublished and ongoing research. Relevant research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
2
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(162 citation statements)
references
References 38 publications
4
147
2
9
Order By: Relevance
“…In the case of an aspired stress reduction, a combination of exercise therapeutic elements with the method of mindfulness-based stress reduction (MBSR) based on Jon Kabat-Zinn ought to be useful for patients under the treatment of HSCT. 61,62 At present, a study funded by the 'German Jose´Carreras Leukemia Foundation' (Project no. R05/33f) to examine such a combined intervention approach is in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of an aspired stress reduction, a combination of exercise therapeutic elements with the method of mindfulness-based stress reduction (MBSR) based on Jon Kabat-Zinn ought to be useful for patients under the treatment of HSCT. 61,62 At present, a study funded by the 'German Jose´Carreras Leukemia Foundation' (Project no. R05/33f) to examine such a combined intervention approach is in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data strengthen evidence for benefits of MBSR (41,53), the real-world feasibility of this intervention is still questionable. Rigorous commitments of time are required for instructors and participants, presenting a potential obstacle to the wide use of MBSR.…”
Section: Sephton Et Almentioning
confidence: 99%
“…Empirical support for the utility of MBSR has been provided by a handful of randomized trials (39,55) reporting benefits with regard to depression in college students (56), medical students (57), and cancer patients (52,53). Segal and colleagues offer convincing evidence that the intervention helps prevent depression relapse (58).…”
Section: Introductionmentioning
confidence: 99%
“…16,18,19 Critical reviews of research using mindfulness as an intervention with cancer outpatients identified its effectiveness in relieving physical and psychological symptoms. [20][21][22][23][24] However, minimal work has been done to apply this intervention among highly symptomatic and distressed patients experiencing an intense and lengthy hospitalization. If feasible, the integration of MM in the HSCT experience has potential to provide patients with coping skills to deal with unpleasant symptoms and an uncertain future.…”
mentioning
confidence: 99%